Evaluating the Application of the RE-AIM Planning and Evaluation Framework: An Updated Systematic Review and Exploration of Pragmatic Application - D'Lima, Danielle; Soukup, Tayana; Hull, Louise (Frontiers in Public Health, 2022)
Abstract Background: RE-AIM is one of the most widely cited and applied frameworks to plan and evaluate the implementation of healthcare and public health interventions. The objective of this review is to provide an updated synthesis of use of the RE-AIM (Reach Effectiveness Adoption Implementation and Maintenance) planning and evaluation framework and explore pragmatic application and how this is reported. Methods: Systematic review. We searched MEDLINE (R) and PsycINFO, via the Ovid interface, between January 2011 and December 2017. Studies that applied RE-AIM as a planning and/or evaluation framework were included. Results: 157 articles met inclusion criteria. 149 reported using RE-AIM for evaluation, three for planning and five for planning and evaluation. Reach was the most frequently reported dimension (92.9%), followed by implementation (90.3%), adoption (89.7%), effectiveness (84.5%), and maintenance (77.4%). 147/157 articles originated from high-income economy countries. Within a sub-set analysis (10% of included articles), 9/15 articles evaluated all dimensions. Of the 6/15 articles that did not evaluate all dimensions, five provided no justification for pragmatic application. Conclusions: RE-AIM has gained increased use in recent years and there is evidence that it is being applied pragmatically. However, the rationale for pragmatic use is often not reported, making it impossible to rule out that key implementation issues have been overlooked. Systematic Review Registration: PROSPERO (CRD42017054616)